Multifunctional role of Nobiletin in cancer chemoprevention: Multifunctional role of Nobiletin in cancer chemoprevention - Malik, Durr-E-Shahwar; Attar, Rukset; Ozbey, Ulku; Romero, Mirna Azalea; Yulaevna, Ishmuratova Margarita; Purenovic, Jelena (Cellular and Molecular Biology, 2022)
The diversity of highly bioactive and pharmacologically active natural products which recognize essential biological targets having exquisite specificity, constitutes a massive pharmacological database for discovery of valuable drugs. The rapid accumulation of information has revealed chemopreventive role of nobiletin against wide variety of cancers. Recent efforts are now being expanded and new integrative omics technologies have illuminated continuously upgrading list of molecular mechanisms which underlie carcinogenesis and metastasis. In this mini-review, we explore the progress that has been made in the identification of promising molecular targets of nobiletin.